Foreign Legal Frameworks in Regulating the Maintenance of Public Safety and Public Order at the Regional Level - Artem Kysko; Maksym Pochtovyi; Serhii Petrov; Andrii Korenev; Roman Mrochko (Nusantara: Journal of Law Studies, 2026)
This article examines foreign legal frameworks governing the maintenance of public safety and public order at the regional level through a comparative legal approach. The study employs a normative juridical method combined with a comparative legal analysis, focusing on statutory regulations, institutional arrangements, and governance practices in selected European Union countries, particularly Germany and Spain. Data are analysed using a qualitative approach to identify patterns in the distribution of authority, coordination mechanisms, and the role of subnational actors in maintaining public order. The findings indicate that effective regulation of public safety at the regional level depends on an optimal balance between decentralisation and centralised coordination, supported by a clear delineation of competencies, a multi-level governance structure, and active public participation. The examined models demonstrate that systems integrating centralised strategic oversight with substantial regional autonomy are more adaptive and responsive to local security challenges. The devolution of powers to regional or autonomous governments enhances institutional flexibility and accelerates responses to public order disturbances. This study contributes to the academic discourse by providing a systematic comparative framework for understanding legal and institutional arrangements in public safety governance at the regional level. It also offers practical insights for policymakers by identifying transferable elements of foreign legal systems that can be adapted to strengthen national legislation and improve the effectiveness of public authorities in maintaining public safety and public order.